PERANGKAT AJAR TULISAN ARAB MELAYU BERBASIS MULTIMEDIA - Novriyanto Novriyanto; Setio Mulyo (UIN Sultan Syarif Kasim Riau, 2011)
Arab Melayu character’s lesson is one of the local lessons that must be taught in SMPN 023 Pekanbaru. In its instruction, founded a number of problems likes the incapacity of SMPN 023 Pekanbaru’s first grade students in reading and writing Arab Melayu characters matching with Arab Melayu writing’s rule in Riau Province. The problem is the description of word writing formula which relied on the witness letter and syllable. This final study analysis the problems of Arab Melayu characters conventionally related to syllabus, RPP and SLP. Furthermore multimedia development which consists of concept, design, material collection, assembly, testing and. Teaching equipment developed is static and consisted of the learning tutorial and questioner. After tested by using blackbox method and user acceptance test, the final output from this application is suitable to the scheme and analysis and also competent to be used as the teaching equipment of Arab Melayu study in SMPN 023 Pekanbaru. Keyword: Arab Melayu Character’s Lesson based on Multimedia, Multimedia